Moya: space, time and sex in an Andean town - Ortiz, Alejandro (1982)
"Male copulating with female", "Garden of the Inca" means Moya, according to current popular knowledge. Somehow these definitions are complemented by those recorded by Quechua dictionaries. We have found two voices: Muya: yes. Garden, orchard (González Holguín, Jesús Lara). Mulla: seems to be a term in direction. It is also used by uncles when they address a younger nephew of a sister and brother (González Holguín, p. 248). A noun derived from the previous one seems to describe the basic social and religious structure of Moya: Mullaypa: s. Esparto rope with three strands, or braid woven with three (González Holguín, p. 248).